Civil defence in Canada 1939-1965 : garnering public support for war and nuclear weapons through the myth of protection - Fisher, Anne Maria (My University, 1999)
The Canadian federal government used a civil defence program to sustain public support for World War Two and afterwards for a defence policy based on nuclear weapons. The successful implementation of civil defence measures depended upon the public's perception of their credibility. During the Second World War, enduring and widespread participation in Canadian civil defence activities suffered because the likelihood of an enemy attack was perceived as being too remote. As Allied victory became more apparent, civil defence was dropped from the government agenda and did not re-emerge until after 1949, when the Soviet Union detonated its first atomic bomb. Civil defence, responding to the perceived threat of an enemy attack, was practiced during the Cold War as part of the military's strategy of nuclear deterrence. Three reasons are identified for public acquiescence and support for a defence policy based on nuclear weapons: censorship of the atomic bombings of Hiroshima and Nagasaki, political restructuring of the post-war international order, and public association of communism with "the enemy." These three issues provided a rationale for a re-emergence of civil defence measures in Canada. An analysis of civil defence pamphlets, municipal survival plans, and mock attack exercises show how civil defence helped convince people that it was possible to survive a nuclear war by minimizing the danger from radioactive fallout and its associated health hazards. However, the credibility of civil defence measures was undermined by the 1954 hydrogen bomb detonation, code named BRAVO, which declassified the occurrence of widespread radioactive fallout. As the dangers of radioactive fallout became better known the federal government increasingly emphasized the individual's responsibility to provide for his or her own survival. A review of civil defence policies in Canadian news magazines (1950-1965) shows a growing public resistance for evacuation and shelters as radioactivity weakens the belief in the possibility of surviving a nuclear war. Canada's civil defence programme was carefully manufactured for very purposeful utilitarian reasons; to demystify an atomic bombing without discussing the human cost. Civil defence strengthened the idea that nuclear weapons could provide for national security. Through civil defence organizations and preparations, public participation was co-opted in favour of nuclear war. By appearing to provide civilians with the means to protect themselves during an attack and the resources to meet their needs in the aftermath of a nuclear war, support was increased for nuclear deterrence.
Keywords: Civil defense Canada History 20th century; Nuclear weapons Government policy Canada; Atomic bomb Canada Safety measures